Analysis Factor Which Influence Sale Volume at Tuberose Business in Desa Pekoren Kabupaten Pasuruan - Putra, Achmad Syaifulloh; Soedarto, Teguh; Rizkiyah, Noor (MediaTrend, 2025)
Indonesia is an agricultural nation that produces a wide range of goods and agricultural goods. Tuberose blooms are one of the agricultural products with a high market value. Because tuberose flowers have a unique scent, there is a lot of market interest in and demand for them. To satisfy these needs and expectations, the appropriate marketing plan is required. This study is to define the features of tuberose flowers and assess the viability of farming in order to ascertain the challenges farmers encounter when trying to market their goods. It will also investigate the impact of tuberose flower costs, demand, and production. The study was carried out in Pasuruan, East Java, in Pekoren Village, Rembang District, from March to September of 2024. This research employs a descriptive methodology that combines farming observation and analysis. It is well known that the age group of 51 to 60 years old accounts for 32% of the characteristics depending on age. The R/C score of 3.75 indicates that growing tuberose is both possible and profitable.